Pemikiran Muhammadiyah dan Muhammad Abduh : suatu studi perbandingan - Lubis, Arbiyah (Jakarta : Bulan Bintang, 1993)
It is a comparative study on thought of Muhammad Abduh, 1849-1905, an Islamic reformer in Egypt, and of Muhammadiyah, a modern Islamic organization in Indonesia
Based on the author's thesis (doctoral--IAIN Syarif Hidayatullah, 1989)
Includes bibliographical references (p. 189-195)
In Indonesia, with some pasages in Arabic
Keywords: Muhammad'Abduh, -- 1849-1905; Muhammadiyah (Organization); Islam -- Indonesia; Islam -- Egypt